Penggunaan Media Sosial dalam Kesehatan Mental Remaja - Asriyanti Rosmalina; Tia Khaerunnisa (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2021)
In this sophisticated technology era, people no longer only interact with other people directly, but also people can interact indirectly, namely with the presence of social media technology. In human life, technological developments are always juxtaposed with modernity which is synonymous with progress. Communities no longer only form communities within an area, but people can form communities with social media. Among the social media users are teenagers. In the use of social media, teenagers usually use it to share about their personal activities, such as their stories and photos with their friends. By using social media, someone is free to comment and share their opinion with other users without any worries. However, in the use of social media, it is often used to create good feelings, without realizing it, social media can backfire on its users so that it can cause bad things. Besides being able to have a strong effect on user behavior, social media can also cause mental health problems for its users.